2022
DOI: 10.34190/ecie.17.1.832
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Blockchain Application to Accounting Education and Accounting Practice

Abstract: Accounting is part of the information system of a company that generates the most important information for the decision-making process. This process should be supported by new technologies to respond to all business requirements. Disruptive technologies change the way of performing business transactions and their implementation in business practice was notably accelerated by the pandemic. In this context, Blockchain technology has been articulated as the future of the accounting profession and there is a grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Based on the findings from Novak, Barišić and Žager (2022), it is concluded that in order to handle blockchain education, accounting instructors must overcome the technical nature of the technology. One of the efforts in place under this development include that conferences and resources which have been provided by American Accounting Association to provide accounting educators with information on blockchain technologies so they can pass it along to their students (Felski & Empey, 2020).…”
Section: Accounting Lecturers' Knowledge and Accounting Graduates' Te...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the findings from Novak, Barišić and Žager (2022), it is concluded that in order to handle blockchain education, accounting instructors must overcome the technical nature of the technology. One of the efforts in place under this development include that conferences and resources which have been provided by American Accounting Association to provide accounting educators with information on blockchain technologies so they can pass it along to their students (Felski & Empey, 2020).…”
Section: Accounting Lecturers' Knowledge and Accounting Graduates' Te...mentioning
confidence: 99%
“…Based on literature search through Google Scholar and Scopus as popular research database, there are quite a number of research papers published globally on the topic related to blockchain technology in various education scopes, but majority are in IT courses. Undeniable, there are also studies which exploring the area of accounting education but most of the research applied qualitative methodology such as systematic literature review, interview, case study, bibliographical research and so on (Al-Htaybat et al 2018;Qasim & Kharbat, 2020;Surianti, 2020;Asonitou, 2020;Samaduzzaman, 2020;Tsiligiris & Bowyer, 2021;Stern & Reinstein, 2021;Novak, Barišić & Žager, 2022). Some of them also developed and proposed education designs/framework such as research conducted by Qasim and Kharbat (2020), and Tsiligiris and Bowyer (2021) on incorporation of blockchain into accounting programme but yet it was merely recommendations and require more in-depth studies on its feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…By integrating blockchain into accounting education, students can gain a deeper understanding of its applications and advantages in accounting. This preparation can help students adapt to the evolving industry and acquire the skills necessary for embracing new technologies (Stern and Reinstein, 2021;Novak et al 2022;Fernandez and Guat, 2023).…”
mentioning
confidence: 99%